(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
This paper examines the impacts of the Mahatma Gandhi National Rural Employment Guarantee Act (MGNREGA) on rural livelihoods in the Ganjam District of Odisha. The study explores MGNREGA’s effects on employment generation, migration patterns, gender equity, and socio-economic advancements. Results highlight that MGNREGA has successfully provided consistent wage employment during lean agricultural periods, reducing dependency on moneylenders and improving living standards. The scheme has curtailed distress migration by offering local work opportunities and empowered women by ensuring substantial participation and equal wages. Challenges remain, including administrative inefficiencies, delayed fund disbursement, and occasional exclusion of marginalized groups. Despite these issues, MGNREGA has significantly contributed to reducing poverty, enhancing food security, and improving social and economic conditions in Ganjam District. This study emphasizes the need for robust implementation mechanisms to maximize the scheme’s benefits.